68Ga-labeled WVP peptide as a novel PET probe for molecular biological diagnosis of unstable thoracic aortic aneurysm and early dissection: an animal study - Lu, Xia; Zhu, Meilin; Zhao, Lingzhou; Qi, Feiran; Zou, Heng; He, Peng; Zhou, Haizhong; Shi, Kuangyu; Du, Jie (Frontiers in Cardiovascular Medicine, 2023)
Objective Type IV collagen (Col-IV) is a prospective biomarker for diagnosing and treating of unstable thoracic aortic aneurysm and dissection (TAAD). This study aims to evaluate the feasibility of 68Ga-labeled WVP peptide (68Ga-DOTA-WVP) as a novel Col-IV-targeted probe for TAAD biological diagnosis using PET/CT. Methods WVP peptide was modified with bifunctional chelator DOTA for 68Ga radiolabeling. Immunohistochemical staining was used to evaluate the expression and location of Col-IV and elastin in aortas treated with 3-aminopropionitrile fumarate (BAPN) at different time points (0, 2, and 4 weeks). The imaging performance of 68Ga-DOTA-WVP was investigated using Micro-PET/CT in a BAPN-induced TAAD mouse model. The relationship between 68Ga-DOTA-WVP uptake in aortic lesions and the serum levels of TAAD-related biomarkers including D-dimer, C-reactive protein (CRP), and serum soluble suppression of tumorigenicity−2 (sST2) was also analyzed. Results 68Ga-DOTA-WVP was readily prepared with high radiochemical purity and stability in vitro. 68Ga-DOTA-WVP Micro-PET/CT could detect Col-IV exposure of unstable aneurysms and early dissection in BAPN-induced TAAD mice, but little 68Ga-DOTA-WVP uptake was shown in the control group at each imaging time point. The differences of Col-IV expression and distribution of 68Ga-DOTA-WVP both in TAAD and control groups further verified the imaging efficiency of 68Ga-DOTA-WVP PET/CT. Additionally, a higher sST2 level was found in the imaging positive (n = 14) than the negative (n = 8) group (9.60 ± 1.14 vs. 8.44 ± 0.52, P = 0.014). Conclusion 68Ga-DOTA-WVP could trace the exposure and abnormal deposition of Col-IV in enlarged and early injured aortas, showing a potential for biological diagnosis, whole-body screening, and progression monitoring of TAAD.